P53 Mediates Amosite Asbestos–Induced Alveolar Epithelial Cell Mitochondria-Regulated Apoptosis - Panduri, Vijayalakshmi (American Thoracic Society, 2006)
Asbestos causes pulmonary toxicity in part by generating reactive oxygen species that cause DNA damage. We previously showed that the mitochondria-regulated (intrinsic) death pathway mediates alveolar epithelial cell (AEC) DNA damage and apoptosis. Because p53 regulates the DNA damage response in part by inducing intrinsic cell death, we determined whether p53-dependent transcriptional activity mediates asbestos-induced AEC mitochondrial dysfunction and apoptosis. We show that inhibitors of p53-dependent transcriptional activation (pifithrin and type 16-E6 protein) block asbestos-induced AEC mitochondrial membrane potential change (ΔΨm), caspase 9 activation, and apoptosis. We demonstrate that asbestos activates p53 promoter activity, mRNA levels, protein expression, and Bax and p53 mitochondrial translocation. Further, pifithrin, E6, phytic acid, or ρ(0)-A549 cells (cells incapable of mitochondrial reactive oxygen species production) block asbestos-induced p53 activation. Finally, we show that asbestos augments p53 expression in cells at the bronchoalveolar duct junctions of rat lungs and that phytic acid prevents this. These data suggest that p53-dependent transcription pathways mediate asbestos-induced AEC mitochondria-regulated apoptosis. This suggests an important interactive effect between p53 and the mitochondria in the pathogenesis of asbestos-induced pulmonary toxicity that may have broader implications for our understanding of pulmonary fibrosis and lung cancer.